Membangun Karakter dan Etika Anak di Taman Baca Victory, Kota Sorong, Provinsi Papua Barat Daya - Natasya Virginia Leuwol; Marissa Swanda Tupamahu (CV. ITTC INDONESIA, 2025)
Strengthening character and ethics from an early age is essential in shaping a morally responsible generation. This community service activity was chosen due to the lack of character development spaces for children outside formal schools. The activity was carried out by second-semester students of the Indonesian Language and Literature Education Study Program, Universitas Victory Sorong, at Victory Reading Garden in Sorong City, as an implementation of the Christian Ethics and Character Education course. Through storytelling, educational games, discussions, and simulations, children were guided to understand values such as honesty, love, and responsibility. The results showed that creative and enjoyable approaches effectively increased children's understanding and participation in learning ethical values. This activity also enriched students' experiences in character building. The results affirm that character education can be effectively instilled through collaboration between higher education institutions and local communities in child-friendly, non-formal learning environments.